2014
DOI: 10.1111/jphp.12261
|View full text |Cite
|
Sign up to set email alerts
|

Catalpol provides protective effects against cerebral ischaemia/reperfusion injury in gerbils

Abstract: These data suggested that the efficacy of catalpol pretreatment on CI/R injury may be attributed to reduction of free radicals and inhibition of lipid peroxidation and ET-1 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 24 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…Catalpol, a major bioactive compound enriched by the dried root of R. glutinosa with the chemical structure previously shown [30], has been found to demonstrate broad and diverse bioactivities including neuroprotection, ameliorating cognition deficits and diabetic encephalopathy, potentially attenuating inflammation-related neurodegenerative diseases, protection against cerebral and cardiac ischemia/reperfusion injury, hepatoprotection, and radioprotection [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Catalpol, a major bioactive compound enriched by the dried root of R. glutinosa with the chemical structure previously shown [30], has been found to demonstrate broad and diverse bioactivities including neuroprotection, ameliorating cognition deficits and diabetic encephalopathy, potentially attenuating inflammation-related neurodegenerative diseases, protection against cerebral and cardiac ischemia/reperfusion injury, hepatoprotection, and radioprotection [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that catalpol, an iridous glycoside, has neuroprotective [13] and cerebroprotective effects [18][19][20]. Catalpol attenuated LPS-induced microglial activation and the expression of ROS, iNOS, NO, and TNF-α [21][22][23]. Catalpol inhibited ischemia-induced apoptosis by modulating Bcl-2 and BAX, increasing the activities of SOD and GSH-Px, and inhibiting the activation of caspase-3 [24][25][26].…”
mentioning
confidence: 99%
“…This iridoid is the main bioactive compound in the dried root of Rehmannia glutinosa, and has been found to have broad and diverse pharmacological activities that include neuroprotection, alleviation of cognitive deficits and diabetic encephalopathy (Jiang et al, 2015). Catalpol potentially attenuates inflammation-related neurodegenerative diseases and offers protection against cerebral and cardiac ischemia/reperfusion injury, as well as hepatoprotection and radioprotection Fu et al, 2014;Huang et al, 2013;Liu et al, 2014;Wang et al, 2010;Zhang et al, 2013Zhang et al, , 2007. In addition, Dong and Chen, (Dong and Chen, 2013), reported that catalpol reduces the kidney weight index, improves kidney function and pathological change, reducing the tissue level of angiotensin II, TGF-1, connective tissue growth factor, fibronectin, and collagen type IV.…”
Section: Iridoid Glycosidesmentioning
confidence: 99%